Lake Bathymetry, Morphometry and Hydrochemistry of Gosaikunda and Associated Lake - Neupane, Basudev; Thakuri, Sudeep; Gurung, Nabin; Aryal, Aavash; Bhandari, Bidhan; Pathak, Kribina (Journal of Tourism and Himalayan Adventures, 2022)
Gosaikunda and Bhairabkunda are two largest lakes among dozens of lakes in the upper Ghattekhola watershed of Trisuli River in Nepal. Although being important high-altitude Ramsar site from Nepal, a detailed inventory that includes essential information on their hydrological, physical, chemical, and biological characteristics and human interactions are missing. We conducted an inventory of the lakes in the watershed in the previous study and in this study; we present the Lake Bathymetry, morphometric characteristics and hydrochemistry following recent methodologies. The Gosaikunda and Bhairbakunda have the maximum depth of 26.5 m and 59.1 m with area of 13.3 and 16 ha, respectively. The study supports to establish a reference site for exploring scientific evidence on the impacts of anthropogenic and climate change on lake hydrological systems in the future.